Getting glucose syrup from cassava starch Manihot and comparative study of the methods of acid and enzymatic hydrolysis - Decheco Egúsquiza, Alicia (2015)
Starch hydrolysis cassava (Manihot esculenta Crantz) to 30% (w/v) was evaluated by the method of acid and enzymatic hydrolysis. In the acid hydrolysis process was evaluated effect of hydrochloric acid in concentrations of 1%, 3% and 5% on the performance of glucose syrup. For enzymatic hydrolysis fungal amylase α 1% was used. There was significant difference between the percentage of reducing sugars and percentage dextrose equivalent (DE) measured for different temperatures liquefaction starch (65, 70 and 75°C) by the α-amylase enzyme at 1%, with 70°C temperature increased activity. For acid hydrolysis significant difference between the percentage reducing sugars and ED percentage measured for various acid concentrations Hydrochloric being the 5% which had higher yields. Comparing both types of hydrolysis was found that there are significant differences between the percentage of sugars and reducing percentage of ED measure acidic and enzymatic hydrolysis of starch cassava, where the enzymatic hydrolysis being a product of greater value was obtained aggregate. Operating conditions and process steps defined.